Dynamics Of Indonesian Agricultural Policy From 1945-2022 - Riezky Ruskandi Natadireja; Sinta Ningrum; Ramadhan Pancasilawan (Eduvest - Journal of Universal Studies, 2024)
Over several decades, agricultural policies have undergone changes considering societal dynamics. The development of land policy changes is divided into three periods: Landreform (1963-1965), National Agrarian Reform Program (PPAN) (2007-2014), and Agrarian Reform (2017-2019). The dynamics of land policies are fundamental for shaping more inclusive and comprehensive policies in the future, as land policies encompass many aspects of social and economic life. The purpose of this research is to describe the development of land policies in Indonesia from 1945 to 2022. The research method used is qualitative with a normative legal approach, exploring principles or standards of positive law. The research findings highlight the agricultural dynamics from the period of President Sukarno to Joko Widodo, focusing significantly on Agrarian Reform, which heavily influences every natural resource. During Sukarno's period, initial national agrarian arrangements were made. Since Soeharto took office, the issue of Agrarian Reform nearly disappeared and was not implemented. President Habibie revived Agrarian Reform. During the leadership of Gus Dur, Megawati, and SBY, they were pioneers of reform after Habibie. During their governance, issue of Agrarian Reform continued to strengthen, alongside the growth of food resources and attention to imported food products and farmers. During President Jokowi's tenure, the concept of Agrarian Reform strengthened further and was demonstrated to the public, successfully enacting implementation regulations. Political considerations related to agrarian issues should at least result in legal order and harmonization of different legal systems. The political connection with national agricultural laws should ideally have beneficial effects in the future.